Pemberdayaan Masyarakat Melalui Pengembangan Sistem Agrosilvopastura Berkelanjutan Berbasis Tanaman Multifungsi di Desa Noekele Kabupaten Kupang NTT - Dwi Wahyuni; Catootjie L. Nalle; Sipora Petronela Telnoni; Hendra Kurniawan; Aisyah Nurdianingsih; Gadis Kartika Pratiwi; Eva Oktaviani; Badia Roy Ricardo Nababan; Kletus Florianus Sera Gare; Dimaz Danang Al-Reza; Khozanah Syifa; Steven Jonathan Adu (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service activity aims to enhance the knowledge and capacity of the Berkat Farmer Group in Noekele Village, Kupang Regency, East Nusa Tenggara, through the implementation of a sustainable agrosilvopastoral system based on multifunctional crops, namely gmelina, Gamma Umami grass, and butterfly pea flowers. The program was implemented using an educative and participatory approach, with evaluation instruments in the form of assessment rubrics analyzed descriptively. The results of the program showed an improvement in community understanding of the agrosilvopastoral concept and the benefits of multifunctional crops in supporting sustainable livestock feed availability. The implementation of the integrated planting system was considered easy to apply and has the potential to improve land-use efficiency, livestock feed stability, and community welfare. This activity demonstrates that an agrosilvopastoral approach based on multifunctional crops is a relevant strategy for sustainable land and livestock management in East Nusa Tenggara.